Protecting Girls from Droughts with Social Safety Nets - Jagori Chatterjee; Joshua D. Merfeld (Institute of Labor Economics (IZA), 2020)
This paper revisits the relationship between agricultural productivity shocks and the infant sex ratio in India and investigates how this relationship changes when households have access to government-provided employment opportunities outside of agriculture. When a household's preference for sons coincides with adverse agricultural productivity shocks, previous research shows that households tend to disproportionately reduce investments (prenatal and postnatal) in their female children. This behavior leads to a relatively more balanced sex ratio in good rainfall years and a more skewed sex ratio (in favor of boys) in inadequate rainfall years. In a deviation from past work, we find evidence of this primarily through prenatal channels in modern India. We then show that a workfare program that decouples both wages and consumption from rainfall attenuates the relationship between rainfall and the infant sex ratio. Using a back-of-the-envelope calculation, we find that the program could have saved at least 0.7 million girls – relative to boys – if the government had implemented it in 2001 to 2005. Additional results on postnatal channels show substantial impacts on the long-term health outcomes of surviving girls, as rainfall no longer differentially affects girls' height-for-age, relative to boys', following the program's implementation.
Keywords: H53; I15; I38; O12; 330; sex ratio; child health; consumption smoothing; workfare program; India